Optimisation of SIMRS Usage for Smooth Internal and External Reporting at Bogor Islamic Hospital - Wa Saruni Batu Atas; Eddy Hermawan Hasudungan; Sri Wahyuni (International Journal of Business, Law, and Education, 2026)
The Hospital Management Information System (SIMRS) plays a strategic role in facilitating effective internal and external hospital reporting. Accurate, timely, and integrated reporting is essential for managerial decision-making and for fulfilling reporting obligations to external stakeholders, including the Health Office and BPJS Health. This study aims to analyse the optimisation of SIMRS utilisation in supporting the efficiency of internal and external reporting at Bogor Islamic Hospital. This research adopts a qualitative descriptive approach, with data collected through observation, in-depth interviews, and document analysis. The findings indicate that the implementation of SIMRS has improved the efficiency of reporting processes. However, several challenges persist, including limited user understanding, suboptimal integration across units, and continued reliance on manual data input. The optimisation of SIMRS—through strengthening human resource competencies, enhancing system functionality, and reinforcing managerial commitment—has been shown to improve the effectiveness of both internal and external reporting processes. It can be concluded that optimising SIMRS utilisation positively impacts the efficiency and reliability of hospital reporting and should be continuously developed to support service quality and good hospital governance.